Produksi dan Mutu Jagung Manis (Zea mays saccharata Sturt.) Akibat Pemupukan Kimia, Organik, Mineral, dan Kombinasinya pada Tanah Inceptisol Kebun Percobaan Fakultas Pertanian Universitas Udayana - MALINDA NOVIARINI; NENGAH NETERA SUBADIYASA; I NYOMAN DIBIA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2017)
The Impact of Chemical Fertilization, Organic, Mineral, and The Combination of Fertilizer towards the Production Number and Quality of Sweet Corn (Zea mays saccharata Sturt.) in Inceptisol Experimental Garden Agriculture Faculty of Udayana University The study aims to figuring out the used of some fertilizers in order to increase the production and the quality of sweet corn in Inceptisols area, and also for figuring out chemicals characteristic and soil fertility in Pegok Village, Denpasar. This research was conducted on August until November 2016, the research took place in the Experimental Garden Faculty of Agriculture, and Soil Laboratory and Environmental Sciences, Faculty of Agriculture, Udayana University. The design method was used for this research was a randomized complete block resign (RCBD) using seven treatments and three-time repetition with the number of plots 21 consist of P0 = Control, P1 = Organic fertilizer, P2 = Mineral fertilizer, P3 = Chemical fertilizer, P4 = Combination Fertilizer (PO + PK), P5 = Combination Fertilizer (PM + PK), P6 = Combination Fertilizer (PO + PM + PK). When the result of variance statistical test shows different result, the procedure followed by LSD method (Least Significance Different) with 95% of confidence level using Costat program. The result of statistical analysis shows the role of chemical fertilizers was proven ability to increase the sweet corn production number, the highest result was 13,97 tons ha-1 which use the P3 treatment (200 kg Phonska and 200 kg Urea) ha-1 increased 110,08%, it showed a better result compared to P0 (Control) which only showing 6,65 tons ha-1. The best quality of sweet corn was shown by P6 formula: the combination of organic, chemical and mineral fertilizer.